Anthropogenic factors in the geomorphological evolution of the NE and E region of the Loutra Aedipsus area (N. Evia-Hellas) - ΠΑΠΑΔΟΠΟΥΛΟΥ-ΒΡΥΝΙΩΤΗ Κ. Α. (Bulletin of the Geological Society of Greece, 2001)
In the region located northeast and east of the Aedipsos Loutra area landforms of anthopogenic origin have been identified. The formation of these landforms has been attributed to morphodynamic processes that related to human interference; the latter is either straightforward, for example following road-construction, quarries or mines or indirect through human activities such as agriculture, stockbreeding and deforestation. Furthermore, it has been identified that the combined action of natural and human factors has caused the formation of the following landforms (ordered from the older to recent ones): (i) Slopes of moderate gradients and valleys of "U" and "V" shape of natural origin (ii) A vegetation-free land-network with tongue-shaped washed surfaces attributed mainly to indirect anthropogenic influence i.e. stock-breeding (iii) Very fine hydrographie network of Badlands type being the product of direct and indirect human interference (iv) Badlands of pyramid form formed directly by the anthropogenic activities. The landforms associated with stockbreeding are responsible for accelerated erosion and irregular water flow; these factors, in association with the local climatological conditions, operating on the tuffite formations has caused the dvelopement of badlands that destroy the existed valleys through the process of erosion. Pyramid badlands on the other side of the highway, connecting the village Aedipsos and Polilofo are the result of the intensive weathering processes following the construction of the road. Finally, active and inactive badlands exist along the coastal road Loutra Aedipsou-Ilia-Limni, with their formation attributed exclusively to anthropogenic factors. The accelerated erosion, responsible for the above mentioned anthropogenic landforms cause often catastrophic phenomena such as landslides, subsidence etc, which has been observed along the road network of the study area. Therefore, the presence of this type of landforms should be taken under consideration for the construction of the various technical works. Besides, the taking of preventive measures, such as the abstraction of soft (erodible) lithological formations, the construction of slopes with small gradients, the avoidance of banking up etc.